The moderating roles of digital marketing and e- commerce on the relationship between it business alignment factors and smes performance in Baghdad City of Iraq - Salim, Ali Mechman (2022)
The IT-business alignment factor has been getting increased amounts of attention from researchers and practitioners due to its potential positive impact on digital marketing and e-commerce performances of the Small and Medium Enterprises (SMEs). This study aims to propose IT-business alignment factors to enhance SME's performances by evaluating the moderating role of digital marketing and e-commerce in the association between IT-business alignment factors and SME's performances sector in Baghdad city of Iraq. To meet these objectives, 18 hypotheses tailored by the resource-based view (RBV) theoretical lenses were proposed to test the theorized relationship of IT business alignment factors, Digital marketing, e-commerce, and SMEs performance. A quantitative method is applied in which data is collected from a customized survey with 65 SMEs functioning in most industries such as communication, investment, and cosmetics sectors in Iraq. The data analysis was conducted using Smart PLS 3.2.9. The data analysis was conducted using Smart PLS 3.2.9. The findings of the path analysis of partial least squares (PLS) support variables in the hypothesized direct relationships with SME's performances. The relationships between IT-business alignment factors (human factors, communication, governance, partnership, competency, IT investment) and SMEs performance (SP) have been supported. Poor of IT business alignment factors, digital marketing, and e-commerce in Iraqi SMEs performance. The finding of digital marketing and E-commerce moderators were supported. The study advances several recommendations that could be beneficial for researchers to conduct further studies in this area as well for the representatives of organizations in their efforts to enhance the SME's performances in the future. Lastly, this research presents theoretical, empirical, and practical implications as well as limitations and recommendations for future investigation.